Transvascular therapy of Hepatocellular Carcinoma (HCC), status and developments. Issue 2 (4th March 2018) - Gnutzmann, Daniel; Kortes, Nikolas; Sumkauskaite, Migle; Schmitz, Anne; Weiss, Karl-Heinz; Radeleff, Boris
Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide. Only 30–40% of patients diagnosed with HCC are candidates for curative treatment options. The remaining majority of patients undergo local, regional or systemic palliative therapies. Transvascular therapy of HCC takes advantage of the fact that hypervascularized HCCs receive their main perfusion from the hepatic artery. In this context transvascular therapy describes different therapies: bland embolization (transarterial embolization, TAE), cTACE (conventional transarterial chemoembolization), DEB-TACE (TACE with drug-eluting beads, DEB) and SIRT (selective internal radiation therapy, radioembolization). cTACE is the most common type of transvascular treatment and represents a combination of the intra-arterial use of a chemotherapeutic agent and embolization. There is no standardized regimen for cTACE. It remains unclear whether the intra-arterial application of a chemotherapeutic agent is definitely required, because bland embolization alone using very small spherical particles shows tumor necrosis comparable to cTACE. For DEB-TACE microparticles loaded with a chemotherapeutic drug combine the advantages of cTACE and bland embolization.